An all-inorganic Li-doped Cs3Cu2I5 single crystal for dual gamma ray and neutron detection applications. Issue 41 (28th September 2022) - Xiang, Peng; Wei, Qinhua; Wang, Chenger; Cai, Peiqing; Tong, Yufeng; Tang, Gao; Sun, Xilei; Yang, Fan; Shi, Hongsheng; Liu, Zugang; Qin, Laishun
Abstract : Study on the growth and scintillation mechanism of Li + -doped Cs3 Cu2 I5 crystal with an excellent FOM value for dual gamma-ray and neutron detection applications. Abstract : Recently, the all-inorganic metal halide Cs3 Cu2 I5 has attracted extensive attention because of its potential use in X-ray and gamma ray detection. Herein, a high-quality and efficient Li + -doped Cs3 Cu2 I5 single crystal with good air stability was grown and utilized for dual gamma ray and neutron detection for the first time. X-ray diffraction, X-ray photoelectron spectroscopy, inductively coupled plasma optical emission spectrometry, and nuclear magnetic resonance were employed to prove that Li + was successfully introduced into Cs3 Cu2 I5, and the lattice sites of Li + were investigated. The photoluminescence quantum efficiency of the Cs3 Cu2 I5 crystal was improved from 83.4% to 88.6% via Li + doping. The photoluminescence and X-ray results showed that the emission peak of Cs3 Cu2 I5 :Li was located at 445 nm and was ascribed to the self-trapped exciton emission. The light yield and energy resolution of the Cs3 Cu2 I5 crystal were significantly improved under 137 Cs irradiation after Li + doping. The effects of the Li + doping on the performance were also investigated. In particular, the Cs3 Cu2 I5 :Li crystal achieved an excellent figure-of-merit of 2.25, which showed its significant potential for dual gamma-ray and neutron detection applications.